COOP 2016: Proceedings of the 12th International Conference on the Design of Cooperative Systems, 23-27 May 2016, Trento, Italy - De Angeli, Antonella; Bannon, Liam; Marti, Patrizia; Bordin, Silvia (Springer International Publishing : Imprint: Springer, 2016)
This volume presents the proceedings of the 12th International Conference on the Design of Cooperative Systems (COOP 2016). The conference is a venue for multidisciplinary research contributing to the design, assessment and analysis of cooperative systems and their integration in organizations, public venues, and everyday life. COOP emerged from the European tradition of Computer Supported Cooperative Work (CSCW) and Cognitive Ergonomics. A collection of 22 papers and 4 workshop overviews are presented, reflecting the variety of research activities in the field of the design of cooperative systems with a special emphasis on "Making Together" This collection offers a broad vision of collective working practices and cooperative design, embracing the idea that design requires a deep understanding of collective activities, involving both artefacts and social practices within a context. The result is a rich and articulated debate that widens the design space towards the exploration of a variety of forms of participation and engagement in collaborative system design. Experienced researchers, academics, designers and practitioners who are interested in collaborative design theory and methods would be interested in the state of the art research and case studies this collection provides.